Optimized design and experiment on ring mold pelletizer for producing biomass fuel pellets - Wei, Gao; Tabil, Lope G; Rongfei, Zhao; Qingyu, Liu (International Journal of Agricultural and Biological Engineering, 2016)
The forming process of biomass fuel pellets using a ring mold pelletizer was analyzed, optimized, tested and evaluated in this study. The effects of stress amplitude and the stress ratio on the fatigue failure of the ring mold under 4-, 3-, and 2-roller designs were investigated. Depending on the calculation of stress amplitude acting on the ring mold, the 4-roller design was chosen for having the smallest value of stress amplitude in this condition. After determining the main design parameters, a three-dimensional model of the ring mold pelletizer was established based on the Pro/Engineer software, and the model was transferred into ADAMS software through Mechanism/Pro which is a dedicated interface software. The ADAMS software was used to run simulations. In order to obtain the highest efficiency and the lowest power consumption, the optimal result was the 4-roller design. Finally, a prototype of the ring mold pelletizer with four rollers was designed and manufactured for biomass fuel pellet production. Corn stover biomass was used as material for experimental manufacturing of fuel pellets. Test and evaluation showed that the optimized pellet durability was 99.79% with ground corn stover particles passing a screen size of 1.97 mm, moisture content of 21.2% w.b. and a material moisture conditioning time of 3.82 h. Pellets formed in the prototype ring mold pelletizer using corn stover had acceptable durability according to European standards. Keywords: biomass pellet, ring mold pelletizer, optimized design, biofuel, corn stover, Pro/Engineer, Adams, pellet durability DOI: 10.3965/j.ijabe.20160903.2074 Citation: Gao W, Tabil L G, Zhao R F, Liu D J. Optimized design and experiment on ring mold pelletizer for producing biomass fuel pellets. Int J Agric & Biol Eng, 2016; 9(3): 57－66.